2013 IEEE International Conference on Green Computing and Communications and IEEE Internet of Things and IEEE Cyber, Physical A 2013
DOI: 10.1109/greencom-ithings-cpscom.2013.171
|View full text |Cite
|
Sign up to set email alerts
|

Community Detection Based on Readers' Borrowing Records

Abstract: Academic libraries have recently adopted recommender systems to provide personalized service for increased library-resource use and personalized educations. Readers' borrowing records help libraries to realize reader preferences and the recommender systems further provide book recommendations for readers. To apply the readers' borrowing records in recommendations, we give some inceptions in this paper. We find out that most of the people only borrow one or two books once a time and the interval between two suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
0
0
1
Order By: Relevance
“…The result is works of Turkish and world literature that are on the reading lists of many readers. Xin et al proposed a community detection-based book recommendation by constructing a similar network of readers [11]. The results of the study, the authors found that most people only borrow one or two books once at a time and the interval between two consecutive borrowing records is usually taken half a month.…”
Section: Fig 1 Communities In a Bipartite Networkmentioning
confidence: 99%
“…The result is works of Turkish and world literature that are on the reading lists of many readers. Xin et al proposed a community detection-based book recommendation by constructing a similar network of readers [11]. The results of the study, the authors found that most people only borrow one or two books once at a time and the interval between two consecutive borrowing records is usually taken half a month.…”
Section: Fig 1 Communities In a Bipartite Networkmentioning
confidence: 99%
“…Keterbatasan penelitian ini adalah belum dilakukan validasi model terkait evaluasi kinerja. Yassine melakukan penelitian pada repositori Khan untuk mengetahui perkembangan komunitas dan kinerja jaringan pembelajaran online dengan menerapkan algoritma deteksi komunitas Parallel Louvain dan Parallel LPA [6]. Li dkk menganalisis topologi jaringan bipartit peminjaman buku di perpustakaan Universitas Shangai, dan mereka mengusulkan sistem rekomendasi buku menggunakan data jaringan [7].…”
Section: Signifikansi Studi a Studi Literatur 1 Kajian Penelitian Ajs...unclassified